Single-level Minimally Invasive Transforaminal Lumbar Interbody Fusion Versus Anterior Lumbar Interbody Fusion for the Surgical Treatment of Isthmic Spondylolisthesis - Patel, Madhav R; Jacob, Kevin C; Pawlowski, Hanna; Prabhu, Michael C; Vanjani, Nisheka N; Singh, Kern (Journal of the American Academy of Orthopaedic Surgeons, 2022)
Limited studies have compared minimally invasive transforaminal lumbar interbody fusion (MIS TLIF) with anterior lumbar interbody fusion (ALIF) for the treatment of isthmic spondylolisthesis. This study aims to compare perioperative variables, patient-reported outcome measures (PROMs), and minimal clinically important difference (MCID) achievement rates between these surgical approaches.INTRODUCTIONLimited studies have compared minimally invasive transforaminal lumbar interbody fusion (MIS TLIF) with anterior lumbar interbody fusion (ALIF) for the treatment of isthmic spondylolisthesis. This study aims to compare perioperative variables, patient-reported outcome measures (PROMs), and minimal clinically important difference (MCID) achievement rates between these surgical approaches.Patients with isthmic spondylolisthesis undergoing primary, single-level MIS TLIF or ALIF were identified in a surgical database. Patients were divided into MIS TLIF and ALIF cohorts. Demographics and perioperative characteristics were collected and compared between groups using the chi square test or Student t-test. PROMs including the Patient-Reported Outcomes Measurement Information System Physical Function, 12-Item Short Form Physical Composite Score, visual analog scale (VAS) back, VAS leg, and Oswestry Disability Index were collected at preoperative, 6-, 12-week, 6-month, 1-, and 2-year time points. Mean PROMs were compared using the Student t-test for independent samples. MCID attainment was determined using established values in the literature; achievement rates by grouping were compared using chi square analysis.METHODSPatients with isthmic spondylolisthesis undergoing primary, single-level MIS TLIF or ALIF were identified in a surgical database. Patients were divided into MIS TLIF and ALIF cohorts. Demographics and perioperative characteristics were collected and compared between groups using the chi square test or Student t-test. PROMs including the Patient-Reported Outcomes Measurement Information System Physical Function, 12-Item Short Form Physical Composite Score, visual analog scale (VAS) back, VAS leg, and Oswestry Disability Index were collected at preoperative, 6-, 12-week, 6-month, 1-, and 2-year time points. Mean PROMs were compared using the Student t-test for independent samples. MCID attainment was determined using established values in the literature; achievement rates by grouping were compared using chi square analysis.One hundred seventy-one patients were included, 121 MIS TLIF and 50 ALIF. No demographic differences were observed. Mean surgical times were 139.7 minutes (MIS TLIF) and 165.5 minutes (ALIF) (P < 0.001). No other perioperative differences were observed. Mean estimated blood loss values were 63.8 mL (MIS TLIF) and 73.7 mL (ALIF). Mean postoperative lengths of stay were 43.9 hours (MIS TLIF) and 42.5 hours (ALIF). Mean PROMs did not markedly differ among groups at any time point. MCID attainment was markedly higher among MIS TLIF patients for the Oswestry Disability Index at 6 weeks (P = 0.046) and 12 weeks (P = 0.007), Patient-Reported Outcomes Measurement Information System Physical Function at 12 weeks (P = 0.015), and VAS leg at 6 weeks (P = 0.031) and 12 weeks (P = 0.045). No other notable differences were observed among MCID achievement by grouping.RESULTSOne hundred seventy-one patients were included, 121 MIS TLIF and 50 ALIF. No demographic differences were observed. Mean surgical times were 139.7 minutes (MIS TLIF) and 165.5 minutes (ALIF) (P < 0.001). No other perioperative differences were observed. Mean estimated blood loss values were 63.8 mL (MIS TLIF) and 73.7 mL (ALIF). Mean postoperative lengths of stay were 43.9 hours (MIS TLIF) and 42.5 hours (ALIF). Mean PROMs did not markedly differ among groups at any time point. MCID attainment was markedly higher among MIS TLIF patients for the Oswestry Disability Index at 6 weeks (P = 0.046) and 12 weeks (P = 0.007), Patient-Reported Outcomes Measurement Information System Physical Function at 12 weeks (P = 0.015), and VAS leg at 6 weeks (P = 0.031) and 12 weeks (P = 0.045). No other notable differences were observed among MCID achievement by grouping.While single-level ALIF demonstrated markedly higher surgical times, other perioperative characteristics and PROMs were comparable among ALIF and MIS TLIF patients. Although MCID achievement rates were generally lower for disability and leg pain among ALIF patients, significance was not reached at 6 months, 1 year, or during the overall postoperative period after fusion.DISCUSSIONWhile single-level ALIF demonstrated markedly higher surgical times, other perioperative characteristics and PROMs were comparable among ALIF and MIS TLIF patients. Although MCID achievement rates were generally lower for disability and leg pain among ALIF patients, significance was not reached at 6 months, 1 year, or during the overall postoperative period after fusion.